Development of Tourist Villages on The Wind (Wawoangi) - Jasiyah, Rabiyatul; Suriadi; Kosilah; Saediman (Research and Social Study Institute, 2022)
The village above the wind (wawoangi) has a high selling value to be used as a superior tourist attraction, but the reality of this village has not been able to be developed as a professional tourist village, both from the aspect of management, human resources, and utilization of village potential. The purpose of developing tourist villages on the wind (wawoangi) is to know the development of tourist villages through analysis of supporting factors and inhibiting tourist villages and the implementation of Sapta Pesona. This community service is carried out so that the public understands about tourism awareness with the tourism potential it has to realize Seven Tourism Charm which can make tourist attractions and tourist attractions more attractive to tourists to visit the village above the wind (Wawoangi). The method performed is qualitative descriptive. Based on the results of community service obtained several alternative strategies that can be applied in the development of tourist villages in wawoangi village related to the desnitasi aspect, industrial aspects, marketing aspects and institutional aspects.